Grammatical Accuracy in Translating Direct Speech: A Comparison between Professionals and EFL Students - Alfarina, Larida; Hartono, Rudi (Universitas PGRI Semarang, 2025)
This study investigates the grammatical accuracy in translating direct speech from This study investigates the grammatical accuracy in translating direct speech from English to Indonesian by comparing the performance of professional translators with that of EFL (English as a Foreign Language) students. The research utilizes 20 carefully selected excerpts from